Lead time performance in the supply chain :|ba case study of the equipment supply environment of the offshore oil exploration and production industry on the UK continental shelf - Nisbet, D. J. (Cranfield University, 2000)
This research study is an examination of the influencing factors on lead time performance in a capital equipment supply environment. The research is being undertaken as a case study of the capital equipment supply environment of the offshore oil exploration and production industry on the UK Continental Shelf. The study methodology is justified as a case supply environment, with multiple sources of data from research instruments including: exploratory and detailed interviews and structured survey methods. The literature review examines time-based approaches to supply chain improvement and the literature related to supply chain integration. Relevant literature related to supply chain systems/structures and relationships/infrastructure are examined as potential influencing factors on lead time performance. A background of the generic case environment is provided, along with relevant literature related to the supply chain in oil exploration and production. The results of a survey of the state of integration of the offshore supply chain are presented and analysed, followed by the results of a structured mail survey within the capital equipment environment. The survey information is used to inform the Case Research phase and define a division of the case environment related to different complexity levels. Individual cases are analysed based on the framework from the literature review and refined from the survey phase. The research questions are addressed at the level of each individual case and propositions derived which are then validated based on cross-case comparisons. Aspects of literature that are supported by the study are discussed along with those areas where there is a contribution to literature. Contribution to supply chain theory is justified related to the derivation of a Types Classification Model as a means of understanding the generic nature of a capital equipment supply chain. Contribution to methodology is justified, based on the use of a supply environment for study and the use of a supply chain trace-back method.